All solid state battery

By using a protective layer with tacky resin and a film between the current collector and the protective layer, the all-solid-state battery reduces the risk of short circuits and prevents current collector damage, enhancing its structural reliability.

JP7666295B2Active Publication Date: 2025-04-22TOYOTA JIDOSHA KK
View PDF 9 Cites 0 Cited by

Patent Information

Application Number
JP2021180220
Authority / Receiving Office
JP · JP
Patent Type
Patents
Current Assignee / Owner
Filing Date
2021-11-04
Publication Date
2025-04-22
Estimated Expiration
2041-11-04

AI Technical Summary

Technical Problem

All-solid-state batteries face the challenge of low adhesiveness between the protective layer and the laminate, which can lead to short circuits when the positive and negative electrode members come into contact during the pressing process.

Method used

Incorporating a protective layer with a resin having tack properties on the side surfaces of the power generation elements, and positioning a film between the current collector and the protective layer to enhance adhesion and prevent damage to the current collector.

Benefits of technology

The high adhesiveness between the protective layer and the laminate reduces the likelihood of short circuits, while the film acts as a cushioning material, preventing damage to the current collector and improving structural reliability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure 0007666295000002
    Figure 0007666295000002
  • Figure 0007666295000003
    Figure 0007666295000003
  • Figure 0007666295000001
    Figure 0007666295000001
Patent Text Reader

Abstract

To provide an all-solid battery which prevents short-circuit.SOLUTION: An all-solid battery has a laminate having a negative electrode current collector, a negative electrode active substance layer, a solid electrolyte layer, a positive electrode active substance layer, and a positive electrode current collector in this order, wherein when the negative electrode active substance layer, the solid electrolyte layer and the positive electrode active substance layer are used as power generation elements, the laminate has a protective layer arranged on a side face of the power generation element, the protective layer contains a resin having tackiness, and the laminate has a film in at least one of between the negative electrode current collector and the protective layer, and between the positive electrode current collector and the protective layer, in cross sectional view in the lamination direction of the all-solid battery.SELECTED DRAWING: Figure 1
Need to check novelty before this filing date? Find Prior Art

Description

[Technical field]

[0001] The present disclosure relates to all-solid-state batteries. [Background technology]

[0002] An all-solid-state battery is a battery having a solid electrolyte layer between a positive electrode and a negative electrode, and has the advantage that it is easier to simplify the safety device compared to a liquid-based battery having an electrolyte solution containing a flammable organic solvent. A laminate having a positive electrode, a solid electrolyte layer, and a negative electrode is usually housed inside an exterior body. It is also known to protect the laminate. For example, Patent Document 1 discloses a secondary battery having a protective member that restricts the contraction and deformation of the exterior body and a movement restriction means that restricts the movement of the protective member to the center in the width direction. [Prior art documents] [Patent documents]

[0003] [Patent Document 1] JP 2020-184518 A Summary of the Invention [Problem to be solved by the invention]

[0004] A protective layer containing a resin may be provided on the side of the laminate. If the adhesiveness between the protective layer and the laminate is low, for example, during pressing to form the laminate, the positive electrode side member and the negative electrode side member may come into contact with each other, causing a short circuit. The present disclosure has been made in view of the above-mentioned circumstances, and has as its main object to provide an all-solid-state battery that is less likely to cause a short circuit. [Means for solving the problem]

[0005] The present disclosure provides an all-solid-state battery including a laminate having an anode current collector, an anode active material layer, a solid electrolyte layer, a cathode active material layer, and a cathode current collector in this order, wherein when the anode active material layer, the solid electrolyte layer, and the cathode active material layer are power-generating elements, the laminate has a protective layer disposed on a side surface of the power-generating element, the protective layer contains a resin having tackiness, and the laminate has a film at least one of between the anode current collector and the protective layer and between the cathode current collector and the protective layer in a cross-sectional view in the stacking direction of the all-solid-state battery.

[0006] According to the present disclosure, since the protective layer contains a resin having tackiness, the protective layer and the laminate have high adhesion, and the all-solid-state battery is less likely to have a short circuit. In addition, since a film is disposed between the current collector and the protective layer, damage to the current collector can be suppressed. Effect of the Invention

[0007] The present disclosure has an effect of providing an all-solid-state battery that is less likely to cause a short circuit. [Brief description of the drawings]

[0008] [Figure 1] FIG. 1 is a schematic cross-sectional view illustrating an all-solid-state battery according to the present disclosure. [Diagram 2] 1A to 1C are schematic cross-sectional views illustrating a method for producing an all-solid-state battery according to the present disclosure. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS

[0009] The all-solid-state battery in the present disclosure will be described in detail below with reference to the drawings. Each of the drawings shown below is a schematic illustration, and the size and shape of each part are appropriately exaggerated to facilitate understanding. In addition, in each of the drawings, hatching showing the cross section of a member is appropriately omitted. In addition, in this specification, when expressing an aspect in which another member is arranged relative to a certain member, simply writing "above" or "below" includes both a case in which another member is arranged directly above or below a certain member so as to be in contact with the certain member, and a case in which another member is arranged above or below a certain member via another member.

[0010] FIG. 1 is a schematic cross-sectional view illustrating an all-solid-state battery according to the present disclosure. The all-solid-state battery 20 shown in FIG. 1 includes two laminates 10 (10A, 10B). The laminate 10A includes a negative electrode current collector 1, a power generating element 2a (negative electrode active material layer 4a, solid electrolyte layer 5a, and positive electrode active material layer 6a), and a positive electrode current collector 3a, in this order. On the other hand, the laminate 10B includes a negative electrode current collector 1, a power generating element 2b (negative electrode active material layer 4b, solid electrolyte layer 5b, and positive electrode active material layer 6b), and a positive electrode current collector 3b, in this order. The laminates 10A and 10B share one negative electrode current collector 1, and are connected in parallel. In addition, the laminates 10 (10A, 10B) include a protective layer 7 disposed on the side of the power generating element 2. In addition, the protective layer 7 contains a resin having tackiness. In addition, the lamination direction D of the all-solid-state battery 20 is a direction in which the power generating element 2a is stacked. L In the cross-sectional view, laminate 10A has a film 8 between positive electrode current collector 3a and protective layer 7. Similarly, laminate 10B has a film 8 between positive electrode current collector 3b and protective layer 7.

[0011] According to the present disclosure, since the protective layer contains a resin having tackiness, the protective layer and the laminate have high adhesion, and the all-solid-state battery is less likely to short circuit. In particular, when the resin having tackiness penetrates into the inside of the power generating element, the adhesion between the protective layer and the laminate is higher. In addition, the high adhesion between the protective layer and the laminate can prevent the positive electrode side member and the negative electrode side member from contacting each other, for example, during pressing to form the laminate. As a result, the battery is less likely to short circuit.

[0012] In addition, since a film is disposed between the current collector and the protective layer, damage (typically breakage) of the current collector can be suppressed. For example, when the laminate is vacuum-sealed inside the laminated exterior body, stress may be concentrated in a region of the current collector located near the end (protective layer) of the laminate, which may cause the current collector to be damaged. In contrast, since a film functioning as a buffer material is disposed between the current collector and the protective layer, damage to the current collector can be suppressed. Therefore, structural reliability is improved. In addition, for example, when the protective layer does not contain a resin having tackiness, the film itself needs to have tackiness in order to ensure adhesion between the protective layer and the film. In contrast, since the protective layer in the present disclosure contains a resin having tackiness, the film itself does not need to have tackiness. Therefore, there is an advantage in that the range of material selection for the film is broadened.

[0013] 1.Laminate The all-solid-state battery in the present disclosure includes a laminate having an anode current collector, an anode active material layer, a solid electrolyte layer, a cathode active material layer, and a cathode current collector in this order. The all-solid-state battery may include only one laminate, or may include two or more laminates. When the all-solid-state battery includes two or more laminates, they may be connected in parallel or in series. In addition, in the present disclosure, the anode active material layer, the solid electrolyte layer, and the cathode active material layer may be referred to as power generating elements.

[0014] (1) Protective layer The laminate in the present disclosure has a protective layer disposed on the side of the power generating element. The protective layer contains a resin having tackiness. "Tackiness" refers to the property of adhering to an adherend in a short time with light force, as defined in JIS Z 0109. "Resin having tackiness" refers to a polymeric material having tackiness. In addition, the "resin having tackiness" is preferably a resin that can achieve a ball number of 5 or more in the ball tack test defined in JIS Z 0237, for example.

[0015] Examples of the resin having tackiness include rubbers such as styrene butadiene rubber, acrylate butadiene rubber, and butadiene rubber; and thermoplastic elastomers. The protective layer may contain only one type of resin as the resin having tackiness, or may contain two or more types of resins. The content of the resin in the protective layer is, for example, 50% by weight or more, 70% by weight or more, or 90% by weight or more. Meanwhile, the content of the resin is 100% by weight or less.

[0016] As shown in Fig. 1, the inner end (the end toward the center of the laminate) of the protective layer 7 is designated as T1, and the outer end (the end opposite the center of the laminate) of the protective layer 7 is designated as T2. The end T1 of the protective layer 7 is preferably in contact with the power generating element 2 (2a, 2b). In addition, as shown in Fig. 1, the current collectors (positive electrode current collectors 3a, 3b in Fig. 1) facing the protective layer 7 via a film 8 may protrude beyond the end T2 of the protective layer 7.

[0017] The tacky resin may penetrate into the inside of the power generating element. For example, in the stacking direction D shown in FIG. L In the direction perpendicular to the arrow A, the distance from the end T1 of the protective layer 7 to the resin that has penetrated to the innermost part of the power generating element 2 (2a, 2b) is defined as L. L is, for example, 50 μm or more, may be 100 μm or more, 500 μm or more, or may be 1 mm or more.

[0018] (2) Film The laminate in the present disclosure has a film between the negative electrode current collector and the protective layer and / or between the positive electrode current collector and the protective layer in a cross-sectional view in the stacking direction of the all-solid-state battery.

[0019] The material of the film is not particularly limited, but may be a resin. Examples of the resin include polyester resins such as polyethylene terephthalate (PET); olefin resins such as polyethylene and polypropylene; acrylic resins; and polyimide resins. In the present disclosure, since the protective layer described above contains a resin having tackiness, the resin contained in the film may or may not have tackiness. The thickness of the film is not particularly limited, but may be, for example, 0.5 μm or more and 300 μm or less.

[0020] It is preferable that the protective layer and the film are in contact with each other. On the other hand, an adhesive layer may or may not be disposed between the protective layer and the current collector. Also, the protective layer and the current collector may be in contact with each other. As shown in FIG. 1, the end portion on the inner side (the center side of the laminate) of the film 8 is designated as T3, and the end portion on the outer side (the side opposite to the center of the laminate) of the film 8 is designated as T4. The end portion T3 of the film 8 may or may not be in contact with the active material layer. On the other hand, as shown in FIG. 1, it is preferable that the end portion T4 of the film 8 protrudes from the end portion T2 of the protective layer 7 described above. This is because the stress concentration at the end portion T2 can be alleviated.

[0021] (3) Laminate The laminate in the present disclosure has a negative electrode current collector, a negative electrode active material layer, a solid electrolyte layer, a positive electrode active material layer, and a positive electrode current collector.

[0022] The negative electrode active material layer contains at least a negative electrode active material, and may contain at least one of a solid electrolyte, a conductive material, and a binder, if necessary. Examples of the negative electrode active material include metal active materials (simple or alloy) such as Si, Sn, Li, In, and Al, carbon active materials such as graphite, and oxide active materials such as lithium titanate. On the other hand, examples of the solid electrolyte include inorganic solid electrolytes such as sulfide solid electrolytes and oxide solid electrolytes. Examples of the conductive material include carbon materials such as acetylene black (AB). Examples of the binder include rubber-based binders and fluoride-based binders. The thickness of the negative electrode active material layer is, for example, 0.1 μm or more and 300 μm or less.

[0023] The positive electrode active material layer contains at least a positive electrode active material, and may contain at least one of a solid electrolyte, a conductive material, and a binder, as necessary. Examples of the positive electrode active material include oxide active materials. Examples of the oxide active material include LiCoO2, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 Examples of the positive electrode active material include rock salt layer type active materials such as O2, spinel type active materials such as LiMn2O4, and olivine type active materials such as LiFePO4. In addition, sulfur (S) or lithium sulfide (Li2S) may be used as the positive electrode active material. The solid electrolyte, conductive material, and binder used in the positive electrode active material layer are the same as those described above, so the description here is omitted.

[0024] The solid electrolyte layer is a layer disposed between the positive electrode active material layer and the negative electrode active material layer. The solid electrolyte layer contains at least a solid electrolyte, and may further contain a binder as necessary. The solid electrolyte and binder used in the solid electrolyte layer are the same as those described above, and therefore will not be described here. The thickness of the solid electrolyte layer is, for example, 0.1 μm or more and 300 μm or less.

[0025] The material of the positive electrode current collector and the negative electrode current collector can be a general material used in all-solid-state batteries. The positive electrode current collector can be, for example, Al, SUS, or Ni. The negative electrode current collector can be, for example, Cu, SUS, or Ni. The shape of the positive electrode current collector and the negative electrode current collector can be, for example, foil, mesh, or porous. The thickness of the positive electrode current collector and the negative electrode current collector is, for example, 1 μm or more and 1 mm or less.

[0026] 2.All-solid-state battery The all-solid-state battery according to the present disclosure generally includes an exterior body that houses the laminate. The exterior body may be a laminate-type exterior body or a case-type exterior body. The all-solid-state battery according to the present disclosure may also include a restraining jig that applies pressure to the laminate in the stacking direction.

[0027] The all-solid-state battery in the present disclosure is typically a lithium secondary battery. The use of the all-solid-state battery is not particularly limited, but examples thereof include power sources for vehicles such as hybrid electric vehicles (HEVs), plug-in hybrid electric vehicles (PHEVs), electric vehicles (BEVs), gasoline-powered vehicles, and diesel-powered vehicles. In particular, it is preferable to use the all-solid-state battery as a driving power source for hybrid electric vehicles, plug-in hybrid electric vehicles, or electric vehicles. In addition, the all-solid-state battery in the present disclosure may be used as a power source for moving objects other than vehicles (for example, railways, ships, and aircraft), and may be used as a power source for electrical products such as information processing devices.

[0028] 3. Manufacturing method of all-solid-state batteries In addition, the present disclosure can provide a method for manufacturing an all-solid-state battery, which manufactures the above-mentioned all-solid-state battery. Specifically, the present disclosure can provide a method for manufacturing an all-solid-state battery, which includes a preparation step of preparing a precursor member having a first current collector and a power generating element formed on at least a first surface side of the first current collector, a protective layer forming step of forming a protective layer on a side surface of the power generating element, a film arranging step of arranging a film on the protective layer in the stacking direction of the precursor member, and a second current collector arranging step of arranging a second current collector on the film in the stacking direction, and in which the protective layer forming step forms the protective layer by applying a coating solution containing a resin having tackiness to the side surface of the power generating element.

[0029] According to the above-mentioned manufacturing method, since the protective layer is formed using a coating solution containing a resin having tackiness, the protective layer and the laminate have high adhesion, and an all-solid-state battery is obtained that is less likely to cause a short circuit. In addition, since a film is disposed between the second current collector and the protective layer, damage to the second current collector can be suppressed.

[0030] (1) Preparation process The preparation step is a step of preparing a precursor member having a first current collector and a power generating element formed on at least a first surface side of the first current collector. The first current collector is a negative electrode current collector or a positive electrode current collector. The negative electrode current collector and the positive electrode current collector are the same as those described in "1. Laminate".

[0031] The power generating element is the same as that described in "1. Laminate". For example, when the first current collector is a negative electrode current collector, the precursor member has a negative electrode current collector, a negative electrode active material layer, a solid electrolyte layer, and a positive electrode active material layer in this order. In addition, the precursor member may have the power generating element formed only on the first surface side of the first current collector, or may have the power generating element formed on both the first surface side and the second surface side opposite the first surface.

[0032] (2) Protective layer formation process The protective layer forming process is a process for forming a protective layer on the side surface of the power generating element. The protective layer is formed by applying a coating solution containing a tacky resin to the side surface of the power generating element. At this time, it is preferable that a part of the coating solution penetrates into the inside of the power generating element. This is because the adhesion between the protective layer and the laminate is higher. The tacky resin is the same as that described in "1. Laminate".

[0033] The coating solution can be prepared, for example, by mixing the above-mentioned resin with a solvent. The solvent in the present disclosure includes not only a solvent that dissolves the above-mentioned resin, but also a dispersion medium that disperses the above-mentioned resin. In addition, it is preferable that the above-mentioned solvent does not react with the solid electrolyte. Examples of the above-mentioned solvent include organic solvents such as diisobutyl ketone (DIBK), butyl butyrate, and tetralin.

[0034] The coating solution preferably has a predetermined viscosity, and the viscosity of the coating solution at room temperature (25°C) is, for example, 400 mPa·s or more, or may be 500 mPa·s or more, or may be 600 mPa·s or more. On the other hand, the viscosity of the coating solution at room temperature (25°C) is, for example, 1000 mPa·s or less, or may be 900 mPa·s or less, or may be 800 mPa·s or less. The viscosity can be adjusted by the type and concentration of the resin.

[0035] The coating solution may be applied to a part or the whole of the side surface of the power generating element. In the protective layer forming step, after the coating solution is applied, it is preferable to volatilize the solvent by drying. The drying may be natural drying or heat drying.

[0036] (3) Film placement process The film disposing step is a step of disposing a film on the protective layer in the lamination direction of the precursor member. The film is the same as that described in "1. Laminate".

[0037] (4) Second current collector placement process The second current collector arrangement step is a step of arranging a second current collector on the film in the stacking direction. The second current collector has the opposite polarity to the first current collector and is a negative current collector or a positive current collector. The negative current collector and the positive current collector are the same as those described in "1. Stack".

[0038] The second current collector disposing step may be performed after the film disposing step, or may be performed simultaneously with the film disposing step. In the latter case, it is preferable to use a member in which a film is disposed on the second current collector.

[0039] (5) Other processes In the present disclosure, after the second current collector arrangement step, a pressing step may be performed in which the precursor member is pressed in the stacking direction.

[0040] The present disclosure is not limited to the above-described embodiment. The above-described embodiment is merely an example, and any configuration that is substantially the same as the technical idea described in the claims of the present disclosure and that exhibits similar effects is included in the technical scope of the present disclosure. EXAMPLES

[0041] [Example 1] (Preparation of precursor material) As shown in FIG. 2(a), a precursor member A was prepared in which a power generating element 2a and a power generating element 2b were arranged on both sides of a negative electrode current collector 1. Specifically, a negative electrode slurry containing a negative electrode active material (Si simple substance), a binder (PVdF-based binder), a sulfide solid electrolyte (Li2S-P2S5-based glass ceramic containing LiBr and LiI), and a conductive material (VGCF) was first applied to one side of a negative electrode current collector (Ni foil, 22 μm) and dried. Next, the negative electrode slurry was applied to the other side of the negative electrode current collector and dried. In this way, a negative electrode in which a negative electrode active material layer was formed on both sides of the negative electrode current collector was produced.

[0042] Next, the positive electrode active material (LiNi 1 / 3 Co 1 / 3 Mn1 / 3 A positive electrode slurry containing O2), a binder (PVdF-based binder), a sulfide solid electrolyte (Li2S-P2S5-based glass ceramic containing LiBr and LiI), and a conductive material (VGCF) was applied onto a substrate (Al foil) and dried. This produced a positive electrode active material layer with substrate.

[0043] Next, a slurry containing a binder (butadiene rubber) and a sulfide solid electrolyte (Li2S-P2S5-based glass ceramic containing LiBr and LiI) was applied onto a substrate (Al foil) and dried, thereby producing a transfer member having a solid electrolyte layer formed on the substrate.

[0044] Next, the negative electrode active material layers arranged on both sides of the negative electrode current collector were faced with the solid electrolyte layers of the transfer member, pressed, and then the substrate was peeled off. The exposed solid electrolyte layers were faced with the positive electrode active material layers of the substrate-attached positive electrode active material layers, pressed, and then the substrate was peeled off. Then, densification pressing, laser trimming, and laser cutting were performed. Thus, a precursor member A was prepared.

[0045] (Formation of protective layer) Styrene butadiene rubber (SBR) was dissolved in diisobutyl ketone (DIBK) to prepare a coating solution. The prepared coating solution was applied to the side of the power generating element of precursor member A and allowed to dry naturally. A pipette with the tip cut off by several millimeters was used for coating. In this way, precursor member A having a protective layer 7 was obtained, as shown in FIG. 2(b).

[0046] (Production of all-solid-state batteries) As shown in FIG. 2(c), a film 8 was placed on each protective layer 7. Next, as shown in FIG. 2(d), a positive electrode current collector 3 (3a, 3b) was placed on the solid electrolyte layer 6 (6a, 6b) and the film 8, and pressed. Although not shown, the positive electrode current collector had an insulating film on the side opposite to the positive electrode active material layer. Then, a battery for evaluation was produced by performing tab welding and lamiseal sealing.

[0047] [Examples 2-3 and Comparative Examples 1-2] An all-solid-state battery was produced in the same manner as in Example 1, except that the resin used in the protective layer was changed as shown in Table 1.

[0048] [evaluation] (Voltage drop) For ten test batteries produced in each Example and Comparative Example, the voltage immediately after the production of the batteries and the voltage after leaving them standing for 72 hours were measured to evaluate the presence or absence of voltage drop. The results are shown in Table 1.

[0049] [Table 1]

[0050] As shown in Table 1, no voltage drop occurred in Examples 1 to 3. On the other hand, a voltage drop occurred in more than half of the batteries in Comparative Examples 1 and 2. This confirmed that the all-solid-state battery according to the present disclosure is less susceptible to short circuits. [Explanation of symbols]

[0051] 1...Negative electrode current collector 2. Power generation elements 3...Positive electrode current collector 4...Negative electrode active material layer 5...Solid electrolyte layer 6...Cathode active material layer 7...protective layer 8. Film 10 ...Laminate 20…All-solid-state battery

Claims

[Claim 1] An all-solid-state battery including a laminate having, in this order, a negative electrode current collector, a negative electrode active material layer, a solid electrolyte layer, a positive electrode active material layer, and a positive electrode current collector, When the negative electrode active material layer, the solid electrolyte layer, and the positive electrode active material layer are used as a power generating element, the laminate has a protective layer disposed on a side surface of the power generating element, The protective layer contains a resin having tackiness, the laminate has a film having no tackiness at least either between the negative electrode current collector and the protective layer or between the positive electrode current collector and the protective layer in a cross-sectional view in a stacking direction of the all-solid-state battery.

Citation Information

Patent Citations

  • Manufacturing method of solid electrolyte battery

    JP2010272368A

  • Self-crosslinkable polyhydroxy polyurethane resin, and method of manufacturing the same

    JP2012007067A

  • Solid-state battery

    JP2014120199A

  • All-solid-state lithium ion battery and method for manufacturing all-solid-state lithium ion battery

    JP2015076179A

  • Lithium ion secondary battery, and method for manufacturing lithium ion secondary battery

    JP2018092886A